1963
DOI: 10.2307/278488
|View full text |Cite
|
Sign up to set email alerts
|

The Trincheras Culture of Northern Sonora

Abstract: Archaeological investigations at La Playa site, 75 miles south of the international border in northern Sonora, Mexico, have yielded detailed information on the Trincheras culture. This culture, which is associated with the drainages of the Magdalena and Altar rivers, is characterized by terraced-hillside sites, rock corrals or enclosures, and a ceramic complex consisting primarily of Trincheras Purple-on-red and Trincheras Polychrome. Intrusions of Trincheras sherds into dated sites of southern Arizona indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…There is no consensus as to why these sites were constructed on hilltops. The most commonly cited interpretation is that they were used as defensive refuges (e.g., Fontana, Greenleaf, and Cassidy 1959;Johnson 1960;Sauer and Brand 1931;Wilcox 1979), although a number of researchers have proposed that some terraces were constructed as agricultural features (Downum, Fish, and Fish 1994;Fish, Fish, and Downum 1984;Huntington 1912). Many investigators have concluded that the cerros de trincheras served multiple functions, particularly as residential villages (e.g., Downum 1993;Downum, Fish, and Fish 1994;Fontana, Greenleaf, and Cassidy 1959;O'-Donovan 1997;Stacy 1974).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is no consensus as to why these sites were constructed on hilltops. The most commonly cited interpretation is that they were used as defensive refuges (e.g., Fontana, Greenleaf, and Cassidy 1959;Johnson 1960;Sauer and Brand 1931;Wilcox 1979), although a number of researchers have proposed that some terraces were constructed as agricultural features (Downum, Fish, and Fish 1994;Fish, Fish, and Downum 1984;Huntington 1912). Many investigators have concluded that the cerros de trincheras served multiple functions, particularly as residential villages (e.g., Downum 1993;Downum, Fish, and Fish 1994;Fontana, Greenleaf, and Cassidy 1959;O'-Donovan 1997;Stacy 1974).…”
Section: Introductionmentioning
confidence: 96%
“…Cerro Juanaquefia overlooks this floodplain, abutting its eastern margin (FIG. 2) Average of 2950 ± 20 first 5 dates *Terrace-Bag-Unit-Depth below surface in cm t Identification by Karen Adams (Hard andRoney 1998b, 1999) :t:Stuiverand Reimer (1993) 910 (1030) Johnson 1960;Sauer and Brand 1931;Stacy 1974;Wilcox 1979). They also have been identified in the Mogollon region of east central Arizona, southern Chihuahua, and in the Rio Sonoran basin in eastern Sonora (Hard and Roney 1998b;O'Donovan 1997;Pailes 1978;Roney in press).…”
Section: Introductionmentioning
confidence: 99%
“…500-505, 627-629;Haury 1976, pp. 305-308;Johnson 1963), and at least occasional Hohokam use of obsidian from the Seri region (Bayman 2007;Bayman and Shackley 1999) may support the notion of ancestral Seri participation.…”
Section: Ceramic Exchange and Assemblage Compositionmentioning
confidence: 63%
“…Otros sitios en las llanuras adyacentes a los cerros de trincheras fueron ocupados de forma contemporánea, por lo que no representan sitios únicos durante ninguna época. Los cerros de trincheras han sido interpretados como refugios defensivos pero también como sitios para agricultura (Huntington 1912; Johnson 1963; Sauer y Brand 1931). En la mayoría de las investigaciones modernas han confirmado las interpretaciones tempranas de que los cerros de trincheras sirvieron como sitios multifuncionales (Fish y Fish 2007; Hard et al 1999; Johnson 1963; Lumholtz 1912; Villalpando y McGuire 2009).…”
Section: Cerros De Trincherasunclassified